O Programa de Educação Tutorial (PET) e a permanência de estudantes na UFMS - Luciana Lopes Ferreira Correa (2021)
The subject of this work is the Tutorial Education Program (PET) and the permanence of students at the Federal University of Mato Grosso do Sul (UFMS). Its general objective is to analyze whether PET contributes to the permanence of UFMS students, having as a time frame the period from 2010 to 2019. Thus, its specific objectives are to study the policies of access and permanence in higher education and their relationship with the Modern State; present the history of PET nationwide; identify the profile of students (scholarship holders and non-scholarship holders) participating in the PET groups at UFMS and verifying whether these students completed their undergraduate courses. For the development of the investigation, we carried out a bibliographic survey of the productions that address the subject, and we analyzed institutional documents, such as Self-Assessment Reports, Institutional Development Plans and normative documents. In order to map the academic and socioeconomic profiles of PETian students, we collected institutional data from the Dean of Undergraduate Studies (Prograd) and the Dean of Student Affairs (Proaes). For analysis and organization of the information, we designed charts, graphs and tables that allowed us to identify the profile of PETian students of the. The research results showed that in the period studied, 1205 students were part of the PET groups at UFMS and that the program, as a qualifying effort in undergraduate education (PRIMÃO, 2015), contributes to the permanence of students, since the absolute majority of PETians completed their undergraduate courses. Regarding the socioeconomic profile of these students, the survey showed that the proportion of female and male students are practically equivalent, and that most of the students are white, single, without children, have no disability, live with their parents, do not work, do not need student assistance, come from public school, have not attended a preparatory course to be admitted to the university, and intend to work and study at the same time after graduating, reaffirming, among the objectives of PET, the preparation of students for the professional market and for the development of postgraduate studies. Keywords: Higher Education; Tutorial Education Program; permanence; socioeconomic profile.